DC side and AC side cascaded multilevel inverter topologies: A comparative study due to variation in design features. (December 2019) - Sajedi, Shahab; Farrell, Michael; Basu, Malabika
Highlights: Comparative Study of AC side and DC side cascaded inverters for HVDC system. Converter loss comparison of 6 design from DC side and AC side cascaded topologies. Output voltage harmonic profile of DC side and AC side cascaded topologies. Comparison of the DC fault current before blocking the IGBT gate signals. Abstract: This paper presents a comparative study between DC side and AC side cascaded topologies for the hybrid modular multilevel converter (MMC) which are becoming popular in recent years. A multilevel converter with half or full bridge sub modules connected across DC link is another alternative for high-voltage applications as it has the same number of sub modules and footprint as AC side cascaded topology with the same DC link voltage and AC side voltage. The compared AC side cascaded structure offers a two-level converter as the high voltage stage and cascaded H-bridge (which is full bridge) sub modules with electrically isolated DC sources or capacitors for the low voltage stages which has number of features suitable for HVDC application. The comparison aspects are investigated against 6 different converter sub module number and configuration options for losses, harmonic profile of the output voltage, and the DC fault current characteristics (before blocking the IGBT gate signals during the DC fault) with the same input DC voltage and the same load for both (DC and AC side) topologies. The major results and findings of this investigation are presented, compared and discussed.